Study skills for health and social care students - Craig, Claire, 1969-; Sage eBooks (London : SAGE, 2009)
This volume provides students with all the skills required for academic study at undergraduate degree level, and then shows them how to develop, transfer and apply these skills to multiple contexts within clinical practice.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Study skills; Social service -- Study and teaching (Higher); Medical care -- Study and teaching (Higher); Electronic books